Ring chromosome 7 syndrome with severe hypertriglyceridemia and mild echocardiographic abnormalities: a case report - Ruiting Ma; Yan Liu; Feng Wei (BMC Pediatrics, 2026)
Abstract Background Ring chromosome 7 [r(7)] is an extremely rare constitutional chromosomal abnormality. The most frequently reported features include growth retardation, pigmented skin lesions, and microcephaly. However, the full phenotypic spectrum remains incompletely defined, particularly with regard to metabolic abnormalities and mild cardiovascular findings. Case presentation We report a 14-year-old Chinese girl referred for severe short stature. She had microcephaly, mild-to-moderate intellectual disability, bilateral epicanthal folds, left strabismus, multiple scattered pigmented melanocytic nevi, a bilateral single palmar crease, and lumbar scoliosis. Laboratory testing revealed severe hypertriglyceridemia (9.19 mmol/L). Echocardiography showed a small pericardial effusion and mild tricuspid regurgitation. Conventional cytogenetic analysis identified a mosaic karyotype of 46,XX,r(7)(p22q36)[56]/45,XX,-7[4], with no normal peripheral blood cell line detected. Whole-exome sequencing did not identify additional pathogenic or likely pathogenic variants relevant to the phenotype. Chromosomal microarray analysis and parental karyotyping were unavailable. Conclusions This case may broaden the reported clinical spectrum of ring chromosome 7 syndrome by highlighting severe hypertriglyceridemia as a potentially under-recognized metabolic manifestation. It also suggests that mild echocardiographic abnormalities may occur in addition to the major congenital cardiac defects described in some previously reported patients. The prolonged diagnostic delay underscores the importance of early chromosomal evaluation in children with unexplained growth failure accompanied by dysmorphic features, neurodevelopmental concerns, or characteristic skin findings.